The Association Between BRCA1 Expression and ER/PR Status in Breast Cancer Patients in NTB - Wulandari, Baiq Nurhandini; Padauleng, Novrita; Lestari, Rizka Vidya; Kumaladewi, Baiq Ratna (Jurnal Biologi Tropis, 2025)
Breast cancer is the most prevalent cancer among women in Indonesia, including in Nusa Tenggara Barat (NTB). Breast Cancer 1 (BRCA1) plays an important role in DNA repair and cell cycle regulation. Altered BRCA1 expression has been associated with the biological characteristics of breast cancer, including estrogen receptor (ER) and progesterone receptor (PR) status, both of which are crucial markers in determining molecular subtypes and predicting responses to hormonal therapy. However, previous studies regarding the association between BRCA1 expression and ER/PR status have shown inconsistent results. This study employed a cross-sectional design involving 50 patients who met the inclusion criteria, namely invasive breast carcinoma patients who had not received chemotherapy. BRCA1 expression was assessed using immunohistochemical staining, with a cut-off of BRCA1 positivity defined as >20% nuclear staining. ER/PR status was obtained from patients’ medical records archived in the Anatomical Pathology Laboratory of NTB Provincial Hospital in 2022–2023. Data processing and analysis were performed using the Chi-square test with a significance level of p < 0.05. Breast cancer patients in NTB demonstrated a balanced distribution of BRCA1 expression, with 50% positive and 50% negative. The majority of patients had ER/PR-positive expression (50%). Among patients with negative BRCA1 expression, 32% were classified as ER/PR-positive subtype. There was no significant association between BRCA1 expression and ER/PR status in breast cancer patients in NTB (p = 0.842). There is no significant association between BRCA1 expression and ER/PR status in breast cancer patients in NTB.